A Case Report of Dental Implants and Site Augmentation in a Patient with Erosive Lichen Planus. (16th May 2022) - Aseri, Abdulrahman
Abstract : Lichen planus (LP) is an autoimmune inflammatory disease that affects oral mucosal tissue, leading to complications in patients treated with dental implant therapy. This case report discusses the clinical management of a patient diagnosed with an erosive type of LP. After disease management, the patient was treated with dental implants in the upper and lower jaws with augmentation procedures around the implants. All implants were loaded after a three-month period of healing. Slight bone loss was observed in the upper premolar area following an exaggerated soft tissue response to the augmentation procedure. Within one year of implant placement, no additional complications were encountered.